The Potential of Dendrocalamus Asper (Betong Bamboo) Leaves as Natural Coagulant for Wastewater Treatment Agent - Mohd Shamsuri, Muhammad Izzwan Syahmi; Che Pa, Nasrul Fikry (Progress in Engineering Application and Technology, 2023)
This study ventured to determine the effectiveness of bamboo leaves to become natural coagulant agent in wastewater treatment since the chemical coagulant produced adverse effect to the environment and human health. This study aims to produce bamboo powder coagulant from Dendrocalamus asper (Betong) type of bamboo via bamboo leaves grinding ball mill machine and to determine adsorbent properties of bamboo powder in jar test at different dosage and pH thus comparing it with commercial coagulant. Turbidity removal of wastewater is further analyzed using turbidity meter and pH meter and bamboo powder further characterize via Fourier Transform Infrared Spectroscopy. Result shows that 15 minutes of grinding with 600 rpm via grinding ball mill machine is sufficient to produce powdered form of bamboo leaves. The turbidity removal via jar test shows that the bamboo leaves powder coagulant were effective at the neutral pH range of 6.5 to 7.5 with the optimum dosage of 70 mg/L. Turbidity removal depicts the counterproductive for dosage below than 50 mg/L and environment that is too basic nor acidic. The bamboo leaves coagulant derived from Dendrocalamus Asper shows potential to compete with commercial coagulant such as Aluminum Sulphate even though the differences in term of turbidity removal percentage is 20 to 30%. FTIR results for functional groups confirmed the presence of protein which act as coagulant properties. Furthermore, the Langmuir adsorption isotherm fits more closely as compared to Freundlich which indicates the adsorption process is monolayer and favorable. Thus, as the adsorbent dosages increases, the bamboo leaves adsorption also increases. This means there will be significant increment in adsorption with further increase of adsorbents dosage. This finding can be set as benchmark of potential bamboo leaves as natural coagulant in treating wastewater treatment instead of using commercial coagulant that affected the environment and human life.